Pengembangan Organisasi Melalui Lokakarya Badan Layanan Umum Daerah - Saiful; Saiful Amri; Syamsul Rizal (Kawanad : Jurnal Pengabdian kepada Masyarakat, 2023)
This activity aims to strengthen the management of Regional Public Service Agencies (BLUD) in the education sector through a series of workshops, training and collaboration with various stakeholders. We identify crucial issues affecting education BLUDs and develop improvement strategies that focus on financial transparency, resource management and organizational independence. Activities involve local government, education BLUD staff, local communities, and advocacy groups. Results include significant improvements in education BLUD financial transparency, increased staff capacity in resource management, and successful piloting of improvement strategies. Improved collaboration between stakeholders is also an important achievement. This activity forms a strong foundation for more efficient and transparent management of education BLUDs. Improvements in the quality of public services in the education sector have become real, while the community feels better benefits. By focusing on developing educational BLUD, this activity strengthens the foundation of education in Aceh Jaya and provides better opportunities for the future of quality education